City networks and the socio-ecological transition. A European inventory - Adrien Labaeye; Thomas Sauer (WWWforEurope, 2013)
Area 5 focuses on the regional and local dimensions of the new European path to socio-ecological transition. Its central assumption is that any strategy developed to enhance a socio-ecological transition is unlikely to yield strong results unless the resources of regional and local actors are mobilised and the complex interactions between central policy initiatives and their regional or local implementation are taken into account. In order to better understand how cities and regions initiate processes of change in relation to sustainability, this milestone focuses on networks of cities, regions and their communities around the issue of sustainable development. Indeed, those networks have often been described in the literature as a crucial element in implementing sustainable development at subnational and local levels and across borders. This milestone takes the form of a short review of the relevant literature that introduces an inventory of the various sustainability networks involving cities and regions across Europe mapping them against a set of established criteria. Findings of the inventory's analysis are presented, some new avenues for research and policy-making being suggested.
Keywords: B4; O18; O52; O57; R11; R23; 330; Academic research; biophysical constraints; ecological excellence; ecological innovation; entrepreneurship; European governance; gender; good governance; green jobs; holistic and interdisciplinary approach; institutional reforms; labour markets; multi-level governance; research; social capital as growth driver; social innovation; socio-ecological transition; sustainable growth; sustainable cities; sustainable urban transition